Pengaruh Media Puzzle Suku Kata Berbasis Kearifan Lokal terhadap Kemampuan Membaca Permulaan dan Minat Membaca di Kelas III MIN 3 Kota Mataram pada Mata Pelajaran Bahasa Indonesia - Lia Handayani; Muammar; Hamzan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to deterMine the effect of local wisdom-based syllable puzzle  media on students’ beginning reading ability and reading interest in grade III at MIN 3 Kota Mataram. The study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample consisted of 37 students in the experimental class and 36 students in the control class. Data were collected through tests, questionnaires, observation, interviews, and documentation. Data analysis included descriptive statistics, normality testing using the Shapiro-Wilk test, and hypothesis testing using the Mann-Whitney U test with the assistance of JASP version 0.19.3.0. The results showed that the experimental class experienced a higher increase in beginning reading ability compared to the control class. The Mean score of the experimental class increased from 57.568 to 82.568, while the control class increased from 57.500 to 67.500. In addition, students’ reading interest in the experimental class was higher, with a Mean score of 87.46 compared to 62.97 in the control class. Hypothesis testing showed a significance value of p < 0.001, indicating that local wisdom-based syllable puzzle  media had a significant effect on students’ beginning reading ability and reading interest.